Golgi-Bypass Is a Major Unconventional Route for Translocation to the Plasma Membrane of Non-Apical Membrane Cargoes in Aspergillus nidulans - Dimou, Sofia; Dionysopoulou, Mariangela; Sagia, Georgia Maria; Diallinas, George (Frontiers in Cell and Developmental Biology, 2022)
Nutrient transporters have been shown to translocate to the plasma membrane (PM) of the filamentous fungus Aspergillus nidulans via an unconventional trafficking route that bypasses the Golgi. This finding strongly suggests the existence of distinct COPII vesicle subpopulations, one following Golgi-dependent conventional secretion, and the other directed towards the PM. Here we address whether Golgi-bypass concerns cargoes other than nutrient transporters, and whether Golgi-bypass is related to cargo structure, size, abundance, physiological function, or polar versus non-polar distribution in the PM. To address these questions, we followed the dynamic subcellular localization of two selected membrane cargoes differing in several of the aforementioned aspects. These are the proton-pump ATPase PmaA and the PalI pH signaling component. Our results show that neosynthesized PmaA and PalI are translocated to the PM via Golgi-bypass, similarly to nutrient transporters. In addition, we showed that COPII-dependent exit of PmaA from the ER requires the alternative COPII coat subunit LstA, rather than Sec24, whereas PalI requires the ER cargo adaptor Erv14. These findings strengthen the evidence of distinct cargo-specific COPII subpopulations and extent the concept of Golgi-independent biogenesis to essential transmembrane proteins, other than nutrient transporters. Overall, our findings point to the idea that Golgi bypass might not constitute a fungal-specific peculiarity, but rather be a novel major and cargo-specific sorting route in eukaryotic cells that has been largely ignored.